Digital and Intelligent Teaching Reform Path of Basic Electrical and Electronic Courses - Li, Lu (Education Insights, 2026)
Against the backdrop of advancing national strategies for modern educational digitalization and deepening New Engineering initiatives, Basic Electrical and Electronic Courses-an essential cornerstone for nurturing engineering talents-have exposed numerous pressing issues in traditional teaching. These include knowledge renewal failing to keep pace with industrial transformations, a clear disconnect between theoretical instruction and engineering practice, and difficulties in implementing personalized education models. Drawing on the mainstream trend of integrating "AI + Education" and referencing the teaching reform experiences of universities such as Guangzhou University and Southeast University, this study delves into feasible pathways for the digital-intelligent transformation of Basic Electrical and Electronic Courses from six core dimensions: renewing teaching concepts, reconstructing curriculum systems, innovating teaching models, upgrading practical platforms, enhancing faculty capabilities, and optimizing evaluation mechanisms. This research aims to establish a digital-intelligent education system supported by technological empowerment, centered on student development, oriented toward competence cultivation, and focused on continuous improvement. It provides referential theoretical insights and practical examples for fostering high-quality engineering and technical talents capable of meeting the demands of industrial digitalization.